Chest Computed Tomography Is an Efficient Method for Initial Diagnosis of COVID-19: An Observational Study - Vieira, Waldonio de Brito; Franco, Karen Margarete Vieira da Silva; Dias, Apio Ricardo Nazareth; Falcão, Aline Semblano Carreira; Falcão, Luiz Fábio Magno; Quaresma, Juarez Antonio Simões; de Sousa, Rita Catarina Medeiros (Frontiers in Medicine, 2022)
Coronavirus disease (COVID-19) is an infectious disease that can lead to pneumonia, pulmonary oedema, acute respiratory distress syndrome, multiple organ and system dysfunction, and death. This study aimed to verify the efficacy of chest computed tomography (CT) for the initial diagnosis of COVID-19 . This observational, retrospective, cross-sectional study included 259 individuals who underwent clinical evaluation, blood collection, chest CT and reverse transcription polymerase chain reaction (RT-PCR) diagnostic test for and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during their course of treatment at a reference hospital in Belém, Pará, Brazil between April and June 2020. Inclusion criteria were flu-like symptoms in adults of both sexes. Individuals with an inconclusive COVID-19 molecular test or who had artifacts in the chest CT images were excluded. Parametric data were analysed using Student-t test, and non-parametric data were analysed using Average test and Fisher exact test. Participants were divided into two groups: Group 1 (COVID-19 positive), n=211 (124 males, 87 females), 51.8+17.9 years old, and Group 2 (COVID-19 negative), n=48 (22 males, 26 females), 47.6+18.6 years old. Most frequent symptoms were cough [Group 1 n=199 (94%) / Group 2 n=46 (95%)], fever [Group 1 n=154 (72%) / Group 2 n=28 (58%)], myalgia [Group 1 n=172 (81%) / Group 2 n=38 (79%)], dyspnoea [Group 1 n=169 (80%) / Group 2 n=37 (77%)], headache [Group 1 n=163 (77%) / Group 2 n=32 (66%)], and anosmia [Group 1 n= 154 (73%) / Group 2 n=29 (60%)]. Group 1 had a higher proportion of ground-glass opacity [Group 1 n=175 (83%) / Group 2 n= 24 (50%), 0.00], vascular enhancement sign [Group 1 n=128 (60%) / Group 2 n=15 (31%), 0.00], septal thickening [ Group 1 n=99 (47%) / Group 2 n=13 (27%), 0.01], crazy-paving pattern [Group 1 n=98 (46%) / Group 2 n=13 (27%), 0.01], consolidations [Group 1 n=92 (43%) / Group 2 n=8 (16%), 0.00], and CO-RADS 4 and 5 [Group 1 n=163 (77.25%) / Group 2 n=24 (50%), 0.00] categories in chest CT. Chest CT, when available, was found to be an efficient method for the initial diagnosis and better management of individuals with COVID-19.